The Influence Of Work Motivation And Job Satisfaction On The Organizational Commitment Of Cv Honda Our Employees - Juniarti (International Journal of Management, Economic and Accounting, 2023)
Organizational commitment is a system or program that has been determined by the company to be implemented and implemented for every human resource (HR) in the company. CV Honda Kita is a company that operates in the field of selling motorbike products. Where the CV Honda Kita company has several problems, namely the problem of work motivation and job satisfaction. The low desire of employees in self-improvement initiatives to master the planned program in achieving the intended targets and goals, the large number of employees who work only as is due to the lack of appreciation given by the company, the many work commitments that have been programmed have not been realized perfectly. The method used in this research is a quantitative approach with quantitative descriptive research in the form of numbers and analysis using statistics. The population in this study were all CV Honda Kita employees, totaling 40 people, who were used as the actual sample in this study, while a sample of 30 for validity testing was used in other companies operating in the same field. The hypothesis results in this study show that work motivation and job satisfaction simultaneously influence employee organizational commitment with a value of Fcount > Ftable (34,194 > 3.25). Where the research results show that simultaneously H1 is accepted and H0 is rejected. The results of this research show that work motivation has a partially positive and significant effect on employee organizational commitment with a value of tcount > ttable (2.866 > 2.02619) and job satisfaction has a partially positive and significant effect on employee organizational commitment with a value of tcount > ttable (2.602 > 2.02619). Simultaneously, work motivation and job satisfaction have a positive and significant effect on the organizational commitment of CV Honda Kita employees and the coefficient of determination value is 63% and the remaining 37% is explained by other variables not examined in this research.